Codesigning an oral healthcare educational intervention for nursing students - Ms Jacqueline Rojo; Professor Ajesh George; Professor Yenna Salamonson; Dr. Leanne Hunt; Professor Lucie M Ramjan (Elsevier, 2023)
Aim or Purpose: To develop an oral healthcare educational intervention for undergraduate nursing students using a codesign framework and to evaluate the process. Materials and Methods: A six-step codesign framework by Dietrich et al. (2017) was used to develop an oral healthcare educational intervention for nursing students. Five academic staff and three nursing students participated in two workshops conducted on Zoom™ to codesign learning activities to be used in the classroom to deliver the oral healthcare learning material. Evaluation of the codesign process was undertaken through focus groups and a hybrid content analysis approach was used to analyse the data. Ethical approval was received from the Western Sydney University Human Research and Ethics Committee (H14177). Results: A multifaceted oral healthcare educational intervention was developed using a range of approaches which included podcasts, dental models, and picture guides. While students were apprehensive about participating alongside faculty staff, good facilitation supported inclusive practices, giving equal voice and respect for all innovative ideas. Critical to the codesign process was adequate resourcing and preparation of participants prior to the workshops to promote robust discussions and meaningful engagement. Conclusions: Codesign facilitated the development of a novel oral healthcare educational intervention for undergraduate nursing students within an Australian nursing education context. The approach was useful in the design of tailored teaching and learning activities that best suited student learning. Each participant brought unique experiences and expertise to the discussion, which led to collaboration between nursing students and academic staff. Good facilitation of the codesign workshops was paramount to the success of the development of the intervention.